FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Atika Dwi Astuti, 13.05.52.0137; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the effect of capital structure, firm size, growth, profitability, systematic risk, and voluntary disclosure of the firm value in the manufacturing companies listed in Indonesia Stock Exchange (IDX). The population in this study is manufacturing companies listed in the Indonesia Stock Exchange (BEI) during of the years 2012-2015. The samples in this study using purposive sampling method. So that, the number of companies included in the criteria for a sample of 54 companies. The data analysis method sused in this study is multiple linear regression analysis. The results showed that the capital structure variables significant negative effect on firm value. Firm size significant positive effect on firm value. Growth is not significant negative effect on firm value. Profitability is not significant positive effect on firm value. Systematic risk is not significant negative effect on firm value. Voluntary disclosure is not significant negative effect on firm value.Keywords: Firm Values, Capital Structure, Firm Size, Growth, Profitability, Systematic Risk, and Voluntary Disclosure